1995
DOI: 10.1016/0896-6273(95)90254-6
|View full text |Cite
|
Sign up to set email alerts
|

Transmitter-mediated inhibition of N-type calcium channels in sensory neurons involves multiple GTP-binding proteins and subunits

Abstract: The modulation of voltage-activated Ca2+ channels by neurotransmitters and peptides is very likely a primary means of regulating Ca(2+)-dependent physiological functions such as neurosecretion, muscle contraction, and membrane excitability. In neurons, N-type Ca2+ channels (defined as omega-conotoxin GVIA-sensitive) are one prominent target for transmitter-mediated inhibition. This inhibition is widely thought to result from a shift in the voltage independence of channel gating. Recently, however, voltage-inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 49 publications
5
89
0
Order By: Relevance
“…Distinct G-protein subtypes serve to transduce activation of various GPCRs. For instance, G i/o transduces the norepinephrine receptor 4,11) , ␥-aminobutyric acid receptor 4) , opioid receptor 33) , serotonin receptor 10) , and somatostatin receptor-modulation 11,21) of VDCCs. G q/11 transduces the muscarinic receptor 23) , neurokinin receptor 23) , and angiotensin II receptormodulation 40) of VDCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct G-protein subtypes serve to transduce activation of various GPCRs. For instance, G i/o transduces the norepinephrine receptor 4,11) , ␥-aminobutyric acid receptor 4) , opioid receptor 33) , serotonin receptor 10) , and somatostatin receptor-modulation 11,21) of VDCCs. G q/11 transduces the muscarinic receptor 23) , neurokinin receptor 23) , and angiotensin II receptormodulation 40) of VDCCs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, G i , G o and G q/11 transduce hormone and neurotransmitter receptormediated modulation of ion channels 4,11,23,40) . In neurons, transmembrane Ca ‫ם2‬ entry via voltage-dependent calcium channels (VDCCs) is of major physiological importance, because several neuronal functions such as neuronal excitability 29) , neuronal migration 28) , neurite outgrowth 25,30,34) , gene expression, and neurotransmitter release, depend on this event.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the effect of PKC on the modulation of N-type channels is clearly demonstrated (Diversé-Pierluissi and Swartz, 1993;Swartz et al, 1993;Yang andTsien, 1993, Diverse-Pierluissi et al, 1995). In many neurons, PKC enhances N-type calcium current via the reversal of tonic G-protein-mediated inhibition (Swartz, 1993;Swartz et al, 1993), and in other studies PKC has been found to increase N-type calcium currents in the absence of G-protein inhibition (Yang and Tsien, 1993) or elicit a steadystate inhibition (Diversé-Pierluissi et al, 1995). Studies of these effects with N-type calcium channels expressed in Xenopus oocytes identified several consensus PKC sites in L I-II of ␣ 1B that are responsible for modulation (Stea et al, 1995;Zamponi et al, 1997).…”
Section: Phosphorylation Of the N-type Calcium Channel In Vivomentioning
confidence: 99%
“…They showed that voltage-independent inhibition (which they called steady-state inhibition) of native N-type currents in chick sensory neurons is triggered by low concentrations of transmitter (GABA and norepinephrine), whereas higher concentrations of transmitter are needed to trigger voltage-dependent inhibition (which they called kinetic slowing). 6 how impoRtAnt is e37a to nociception? N-type channels in nociceptors are implicated in chronic pain.…”
Section: What Took Us So Long?mentioning
confidence: 99%
“…Combined with our previous studies that show enrichment of e37a in nociceptors, 5 our data suggest a molecular basis for the high susceptibility of N-type currents in sensory neurons to voltage-independent inhibition following G protein activation. 6 opening the gAte to g pRotein-meDiAteD inhibition N-type calcium channels in most neurons are susceptible to inhibition by G protein activation. 7,8 This ubiquitous form of inhibition is voltage-dependent and mediated by G protein Gbg dimers.…”
Section: Introductionmentioning
confidence: 99%